The Rights of Nature: “Manglares” and “Bosque Protector Los Cedros” Judgments - Piedra Vivar, Pablo Arturo (2024)
This article analysis the decisions of the Constitutional Court in the “Manglares” case and in the “Bosque Protector Los Cedros” case. The analysis extracts the elements of the rights of nature in the Ecuadorian constitution and compares them with the decisions of the Constitutional Court. In order to carry out this exercise, a critical analysis of the judgments was used. It compares what was developed with the concepts used by the natural sciences and determines whether the concepts developed can be improved and which of these concepts have yet to be developed by the Court. This comparison showed that it is necessary to continue developing a deeper dialogue with the natural sciences in order to understand and explain the elements of nature. The current Constitution of Ecuador incorporated the rights of nature for the frst time in our constitutional history. Despite some favorable rulings by judges of frst instance and Provincial Courts, the Constitutional Court, the highest body of consti tutional justice in the country, had not issued rulings that develop these rights until recently.